Seventh Joint Meeting of K-J-CaP and CaPSURE: extending the global initiative to improve prostate cancer management - Akaza, Hideyuki (Asian Pacific Prostate Society (APPS), 2014)
This report summarizes the presentations and discussions that took place at the Seventh Joint Meeting of the Korea–Japan Study Group of Prostate Cancer (K-J-CaP) and the Cancer of the Prostate Strategic Urologic Research Endeavor (CaPSURE) held in Seoul, Korea, in September 2013. The original J-CaP and CaPSURE Joint Initiative has now been established since 2007 and since the initial collaboration between research teams in the United States (US) and Japan, the project has expanded to include several other Asian countries. The objective of the initiative is to analyze and compare data for prostate cancer patients in the participating countries, looking at similarities and differences in patient management and outcomes. Until now the focus has been primarily on data generated within J-CaP and CaPSURE, both large-scale, longitudinal, observational databases of prostate cancer patients in Japan and the US, respectively. This year’s meeting was hosted for the first time in Korea which has recently established its own national database–K-CaP–to add to the wealth of data generated by J-CaP and CaPSURE. As a newly-developed database, K-CaP has also provided a valuable ‘template’ for other countries, such as China and Indonesia, planning to establish their own national databases and this will ultimately allow greater opportunities for international data comparisons. A range of topics was discussed at this Seventh Joint Meeting including comparison of outcomes following androgen deprivation therapy or radical prostatectomy in patients with localized prostate cancer, the use of active surveillance as a treatment option and the triggers for intervention when employing this regimen, patient quality of life during treatment, the impact of comorbidities on outcomes, and a comparison of recent outcomes data between J-CaP and CaPSURE. The participants recognized that prostate cancer was now a global disease and therefore major insights into understanding and improving the management of this condition would arise from global interactions such as this joint initiative.